Mother’s Knowledge and Attitude Associated with Acute Respiratory Infection Prevention in Under Two Children in Lewoleba, East Nusa Tenggara, Indonesia - Astiarani, Yunisa; GAI Kedang, Maria; Jena, Yeremias; Santi, Bryany Titi (School of Medicine and Health Sciences, Atma Jaya Catholic University of Indonesia, 2023)
Introduction: This study investigates the correlation between maternal knowledge and attitudes and their impact on preventing Acute Respiratory Infections (ARIs) in under two children in Lewoleba, East Nusa Tenggara, Indonesia. With a focus on this region with limited prior research, the study explores howa mother's understanding and approach toward ARI prevention measures may contribute to improved child health outcomes. Methods: A cross-sectional study investigated the association between maternal knowledge and attitudes and their impact on preventing ARIs in children under two years old in Lewoleba, East Nusa Tenggara, Indonesia. The study administered structured questionnaires to gather data on maternal knowledge and attitude toward ARIs, behavior toward prevention, and demographic information. Data were analyzed using bivariate analysis to evaluate the association. Results: Of 144 respondents, 81.3% showed high ARI knowledge, but only 54.9% had positive attitudes, and 53.2% exhibited good behaviors. The Chi-square test revealed a significant relationship between knowledge and attitude with ARI behavior (P<0.05) among mothers with children aged 0-24 months in Lewoleba Primary Health Centre, Nubatukan District, Lembata Regency. Specifically, mothers with high knowledge had a 2.31 prevalence ratio (PR) for good ARI-related behaviors compared to those with low ability. In contrast, those with positive attitudes had a 1.52 PR for such behaviors. Conclusions: This study revealed a connection between mothers' knowledge and attitudes concerning ARI in children under two and their preventive actions. Despite a relative scarcity of good behaviors compared to strong knowledge and positive attitudes, the findings underscore that higher knowledge scores and more positive attitudes lead to significantly better behavioral outcomes. Keywords: acute respiratory infections - attitude - behavior - knowledge - prevention.